Comparison of SUPG with Bubble Stabilization Parameters and the Standard SUPG - Xiaowei Liu; Jin Zhang (Abstract and Applied Analysis)
We study a streamline upwind Petrov-Galerkin method (SUPG) with bubble stabilization coefficients on quasiuniform triangular meshes. The new algorithm is a consistent Petrov-Galerkin method and shows similar numerical performances as the standard SUPG when the mesh Péclet number is greater than 1. Relationship between the new algorithm and the standard SUPG will be explored. Numerical experiments support these results.